Comparative Effectiveness of Enhanced Recovery After Surgery Program Combined With Single-Incision Laparoscopic Surgery in Colorectal Cancer Surgery: A Retrospective Analysis - Wang, Changgang; Feng, Haoran; Zhu, Xiaoning; Song, Zijia; Li, You; Shi, Yiqing; Jiang, Yimei; Chen, Xianze; Zhang, Tao; Zhao, Ren; Liu, Kun (Frontiers in Oncology, 2022)
Background: This study aimed to evaluate the safety and advantages of ERAS combined with single-incision laparoscopic surgery (SILS) in CRC surgery. Methods: This was a retrospective study of patients with CRC who underwent surgery between April 2018 and April 2020 in Ruijin Hospital North, Shanghai Jiaotong University School of Medicine. The patients were divided into three groups: group A (n=138), patients who underwent traditional multiport laparoscopic colectomy with conventional perioperative management; group B (n=63), patients who underwent SILS; and group C (n=51), patients who underwent SILS with ERAS. Results: Overall, 252 participants were included in the retrospective study. The mean operation time (min) in group B and group C was shorter than that in group A (p=0.004). The estimated surgical blood loss (ml) was lower in groups B and C than in group A (p=0.011). The length of surgical incision (cm) was shorter in groups B and C than in group A (p＜0.001). The time before first flatus (hours) in group C was shorter than in groups A and B (p<0.001). The days prior to the administration of free oral fluids in group C was shorter than in groups A and B (p<0.001). The days of prior solid diet was less in group C than in groups A and B (p=0.027). The postoperative length of stay (LOS) was less in group C compared with that in groups A and B (p=0.023). The visual analog scale (VAS) scores on day 0, 1, and 2 in groups B and C were lower than those in group A (day 0, p<0.001; day 1, p<0.001; day 2, p=0.002), while the VAS score on day 3 showed no differences in the three groups (p=0.018). Conclusion: The findings suggest that SILS combined with ERAS may be a feasible and safe procedure for CRC surgery because it provides favorable cosmetic results, early dietary resumption, shorter hospital stays, and appropriate control of postoperative pain without increases in complications or readmission rates compared to conventional perioperative care with SILS or conventional laparoscopic surgery of CRC. Further prospective randomized controlled studies are needed to enhance evidence-based medical evidence.